The Rate of Oral Lesions in Infants and Neonates Attend Maternity and Pediatric Teaching Hospital in Sulaymaniyah City - Muhammed Ali Hassan , Shaida; Taha Garib, Balkess (Diyala Journal of Medicine, 2021)
Background: The prevalence of oral mucosal lesions in infants and neonates is still a matter of debate. Objective: To find the frequency of oral mucosal lesions in children from Sulaymaniyah city. Patients and Methods: A cross-sectional study was performed in Maternity and Pediatrics Teaching Hospitals in Sulaymaniyah city. Twohundred children aged from birth to two years old were randomly selected. Demographic features, mode of delivery, pattern of feeding, and type and site of oral mucosal lesions, were recorded. Results: Male: female ratio was 1.06:1, and 64% were delivered by cesarean section. Significant differences were present between breastfeeding with the mode of delivery and age of the infants. Oral mucosal lesions were observed in 64.5% of children at 141 sites. 30% of lesions are located at median palatine raphe. The diagnosis of 30% of oral mucosal lesions was Epstein pearls, and 16% were Bohn’s nodule. The oral mucosal lesions were more frequently seen in children within the first week. Conclusion: About three-quarters of children was afflicted with oral mucosal lesions. Besides, Epstein pearls and Bohn’s nodule were among the most frequent diagnosis. Further, ages of a week or less afflicted more with congenital oral mucosal lesions.